Using PIM-Taiwan, PRISCUS, and Beers criteria to assess potentially inappropriate medication use among older adults with 90-day rehospitalization: a population-based study in Taiwan - Hsieh, Kun-Pin; Huang, Ru-Yu; Yang, Yi-Hsin; Ho, Pei-Shan; Chen, Kuang-Peng; Tung, Chun-Liong; Chu, Ya-Lan; Tsai, Jui-Hsiu (Frontiers in Pharmacology, 2023)
Background: Multimorbidity and polypharmacy increase the risk of hospitalization in older adults receiving potentially inappropriate medication (PIM). The current study compared the ability of PIM-Taiwan, PRISCUS, and Beers criteria to predict 90-day rehospitalization in older patients with and without PIM.The retrospective cohort study used Taiwan's Longitudinal Health Insurance Database to retrieve quarterly information about prescribed medication for adults aged ≥65 years hospitalized between 2001 and 2018. We analyzed the association of PIM with 90-day rehospitalization using logistic regression.The study cohort included 206,058 older adults (mean age: 72.5 years). In the analysis, 133,201 (64.6%), 97,790 (47.5%), and 147,450 (71.6%), were identified as having PIM exposure in PIM-Taiwan, PRICUS, and Beers criteria, respectively. PIM-Taiwan criteria found exposure to PIM affecting the cardiovascular (adjusted OR [aOR] 1.37, 95% confidence interval [CI]=1.32-1.41), gastrointestinal (aOR 1.26, 95% CI=1.23-1.30), central nervous (aOR 1.11, 95% CI=1.08-1.14), and respiratory (aOR 1.16, 95% CI=1.12-1.20) systems significantly increased the risk of 90-day rehospitalization, after adjustment for covariates. In PRISCUS criteria, exposure to PIM affecting the respiratory (aOR 1.48, 95% CI=1.41-1.56), central nervous (aOR 1.21, 95% CI=1.09-1.15), and cardiovascular (aOR 1.20, 95% CI=1.16-1.24) systems significantly increased the risk. In Beers criteria, exposure to PIM affecting the cardiovascular (aOR 1.37, 95% CI=1.32-1.41), gastrointestinal (aOR 1.38, 95% CI=1.35-1.42), central nervous (aOR 1.18, 95% CI=1.15-1.21), endocrine (aOR 1.10, 95% CI=1.06-1.15), and respiratory (aOR 1.09, 95% CI=1.04-1.13) systems significantly increased the risk. Patients with 90-day rehospitalization had higher rates of the potentially harmful drug-drug interaction (DDI) pairs of serotonin syndrome (n=19; 48.8%), QT prolongation (n=4; 30.8%), extrapyramidal symptoms (EPS) (n=102; 24.5%), and hypokalemia (n=275; 20.1%).Beers criteria was more efficient in predicting 90-day rehospitalization among older adults experiencing PIM in Taiwan than either PIM-Taiwan or PRISCUS. The risk of 90-day rehospitalization was associated with the potentially harmful DDI classes of serotonin syndrome, QT prolongation, EPS, and hypokalemia.